THE EFFECT OF MOTIVATION, COMPETENCE, AND COMPENSATION ON EMPLOYEE PERFORMANCE IMPROVEMENT - Wydyanto, Wydyanto; M. Rizky Mahaputra (Dinasti Publisher, 2021)
In a company, employees are one of the most important elements to achieve company goals. The performance of an employee is certainly influenced by several factors that a manager needs to know. Managers must know the strengths and weaknesses of each manager in order to maximize the potential and minimize the shortcomings of employees. Factors that affect the performance of an employee are motivation, compensation, and competence. Motivation is needed by an individual because basically humans need encouragement or encouragement in order to work better. Motivation is given as a way to improve employee performance to carry out their responsibilities. The different competencies of each employee are also a factor in the good or bad performance of an employee. Competence in each employee must be improved in order to achieve company goals. Compensation also affects an employee's performance. Compensation can be in the form of money or other facilities. Compensation is given as remuneration by the company to employees who have carried out their duties and responsibilities.